Copper recovery in a bench-scale carrier facilitated tubular supported liquid membrane system - Makaka S.; Aziz M.; Nesbitt A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The extraction of copper ions in a tubular supported liquid membrane using LIX 984NC as a mobile carrier was studied, evaluating the effect of the feed characteristics (flowrate, density, viscosity) on the feedside laminar layer of the membrane. A vertical countercurrent, double pipe perspex benchscale reactor consisting of a single hydrophobic PVDF tubular membrane mounted inside was used in all test work. The membrane was impregnated with LIX 984NC and became the support for this organic transport medium. Dilute Copper solution passed through the centre pipe and sulphuric acid as strippant passed through the shell side. Copper was successfully transported from the feedside to the stripside and from the data obtained, a relationship between Schmidt, Reynolds and Sherwood number was achieved of.